Assessment of Health Indicators in Individuals with Intestinal Stoma using the Nursing Outcomes Classification: A Cross-Sectional Study - Moya-Muñoz, Noelia; Armenteros-Fernández, Elena; Bautista-Mártir, Clara; Vílchez-Díaz, Irene Del Pilar; López-Medina, Isabel María; Montoya-Juárez, Rafael; Hueso-Montoro, César; Capilla-Díaz, Concepción (Frontiers in Surgery, 2022)
Aim: To determine nursing outcomes in individuals with intestinal stoma and the relationships between them and sociodemographic and clinical variables. Design: Cross-sectional study performed with 102 subjects at the General Surgery Unit of a first-level hospital. Methods: Data on the presence of nursing outcomes were collected using the Nursing Outcomes Classification. Data on sociodemographic and clinical variables were also collected. Univariate and bivariate data analyses were performed. Results: Outcomes related to participation in making health decisions and knowledge of ostomy care were assessed across the study sample. Period of care (post-operative and follow-up) was the most common significant variable (p < 0.05) among the outcomes. The outcome scores ranged from 2 to 3, indicating a moderate level of impairment in the physical, psychological, and social spheres of these patients. The scores in the indicators on Participation in making health decisions and Knowledge of stoma care improved in the period of continuity of care compared to the postoperative period, being this difference statistically significant (p<0.001). Conclusions: The care plan for individuals with intestinal stoma needs to include indicators measuring patient participation in making decisions related to their condition, as well as indicators related to their knowledge and self-care of their stoma. Relevance to clinical practice: This study aims to determine the nursing outcomes in individuals with intestinal stoma and the relationships between them and sociodemographic and clinical variables. It provides the opportunity to plan achievable objectives with patients using a system of indicators that facilitate their assessment and monitoring.